2005
DOI: 10.2174/1570161053586868
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of Leptin and Ghrelin in Cardiovascular Physiology and Pathophysiology

Abstract: Leptin and ghrelin are novel peptide hormones which are counter-regulatory in the central control of appetite. More recently, it has become clear that these hormones have a range of effects on the cardiovascular system. Leptin increases sympathetic activity, producing a pressor effect when acting on the central nervous system. However, leptin produces vasodilation by an endothelium-dependent mechanism peripherally. Ghrelin decreases sympathetic activity and has a depressor effect when acting on the central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 159 publications
(193 reference statements)
1
38
1
Order By: Relevance
“…Leptin was also reported to stimulate calcification of endothelial cells in vitro, which may indicate an increased risk of atherosclerosis. [23,36] Although previous studies reported the association between plasma leptin levels and ED in diabetic patients, [34] such an association was not noted in the present study, in which the diabetics were excluded.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Leptin was also reported to stimulate calcification of endothelial cells in vitro, which may indicate an increased risk of atherosclerosis. [23,36] Although previous studies reported the association between plasma leptin levels and ED in diabetic patients, [34] such an association was not noted in the present study, in which the diabetics were excluded.…”
Section: Discussioncontrasting
confidence: 72%
“…[2,4,23] In the present study, plasma ghrelin levels were significantly higher in patients with normal coronary microvascular and endothelial functions as compared to patients with ED. Although not statistically significant because of the low patient number, a weak correlation also existed between serum ghrelin levels and CFR values.…”
Section: Discussionsupporting
confidence: 50%
“…Leptin has been suggested to have a role in cardiovascular system physiology and pathophysiology. 17 The effect of leptin on cardiac physiology, however, is controversial. Although high doses of leptin (10-1000 nmol l À1 ) seem to directly suppress cardiac contraction in isolated cardiomyocytes, 16 physiologically relevant concentrations (25 ng ml À1 ) abolish the negative inotropic effect of IL-1b, 18 suggesting a potential role of leptin in modulating proinflammatory effects in the heart.…”
Section: Role Of Adipose Tissue In Cardiac Dysfunction C Look Et Almentioning
confidence: 99%
“…2, 3 Moreover, there is increasing evidence for a cardiovascular function of ghrelin. Ghrelin has been postulated to exert a protective effect against atherosclerosis by anti-inflammatory, 4 vasodilatory 5 and antioxidant effects, 4 as well as through improved endothelial function. 6 Furthermore, a radiolabeled ghrelin [ 125 I-His9] has been shown to bind to the heart and peripheral vascular tissues.…”
Section: Introductionmentioning
confidence: 99%